1996
DOI: 10.1051/mmm:1996118
|View full text |Cite
|
Sign up to set email alerts
|

Order and Disorder in Boron Phases

Abstract: Abstract. 2014 The complicated rhombohedral unit cell of crystalline 03B2-boron containing 105 atoms is a good approximant structure for a quasicrystal. Thus one may wonder if between the amorphous and the crystalline phases of boron, a non-metallic quasi-crystalline phase could exist. In order to examine this possibility and to characterize order and disorder in boron phases, we have performed high resolution electron microscopy (HREM) and electron energy loss spectroscopy (EELS) measurements. In the crystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

1998
1998
2003
2003

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…They distort the crystal only slightly because they preserve the rhombohedral symmetry and the structure of the icosahedron. In B 4 C ceramics obtained by hot pressing, however, these defects can be as close as a few lattice parameters [18], and the low-frequency part of the Raman spectrum is quite different from those of Fig. 3.…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…They distort the crystal only slightly because they preserve the rhombohedral symmetry and the structure of the icosahedron. In B 4 C ceramics obtained by hot pressing, however, these defects can be as close as a few lattice parameters [18], and the low-frequency part of the Raman spectrum is quite different from those of Fig. 3.…”
mentioning
confidence: 87%
“…For this reason the apparent bulk modulus of the icosahedra, which was found smaller than B 0 , might need to be verified in a quasi hydrostatic environment, with an accurate measurement of pressure. Moreover, twinning in boron allows the crystal to accommodate large strains and to prevent the formation of quasi-crystalline phases [18]. We are inclined to attribute the observed anti-molecular compression to pressure inhomogeneities induced by the intensive twinning in B 4 C ceramics.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Notably, it contains a fairly large concentration of Boron. Owing to the prevalence of icosahedra in elemental Boron, researchers have long suggested that icosahedral quasicrystals might occur in Boron-rich compounds [13,14,15,16,17,18], but none has yet been found.…”
Section: Boron-containing Phasesmentioning
confidence: 99%
“…Several reviews exist to cover the results obtained up to 1983 (Pearson, 1972;Matkovich, 1977;Kuz'ma, 1983). Boron also exists in an amorphous state which has been studied recently by transmission electron microscopy (Favia et al, 1996).…”
Section: Introductionmentioning
confidence: 99%